Food poisoning outbreak caused dioscorea hispida dennst in Gading 10 Village, Gunung Kidul, Yogyakarta august 2020: a case report study - Ayu Cahyaningtyas; Aryanto, Samsu; Hidayati, Titiek (BKM Public Health and Community Medicine, 2021)
Objective: On August 12 2020, a food poisoning outbreak occurred in Gading 10 Village Gunung Kidul District. Health office of Gunung Kidul District were revealing three attendances who hospitalized in the hospital of Nur Rohmah after consuming gadung tubers (dioscorea hispida dennts.) and one of them passed away. Based on the information, we were doing an epidemiological investigation immediately to make sure of the existence of the outbreak. This study aimed to investigate the causative agents, source of food poisoning and mode of food poisoning transmission in Gading 10 Village. Method: This epidemiological investigation was using case report study design. Case defined as any residence who consumed gadung tubers in Gading 10 Village on August 12 2020. The data were collected using food poisoning questionnaire and medical record. Results: Based on the investigation results, three villagers who consumed gadung tubers were ill (100%) and one of them) was passed away (33,33%). The incubation period was around 5 minute until 4 hours. The predominate symptoms were vomiting, nausea, and headache. Gadung tubers (dioscorea hispida dennts.) was determined as the source of this food poisoning outbreak. Based on the incubation period and symptoms to the comparison diagnosis, dioscorine agent are suspected to be the cause of this food poisoning outbreak. Conclusion: The most likely source of contamination based on incubation period and symptoms was Dioscorine. Food poisoning outbreak was occurred in Gading 10 Village, Gunung Kidul District on August 12 2020. We recommend strengthening intervention community health education about safe processing gadung tubers for consumption.